2015
DOI: 10.1371/journal.pone.0144737
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Mitochondrial Ca2+-Sensitive Potassium (mBKCa) Channels in Sildenafil-Induced Cardioprotection in Rats

Abstract: BackgroundMitochondrial large-conductance Ca2+-sensitive potassium (mBKCa) channels are involved in myocardial ischemic preconditioning. Their role in sildenafil-induced cardioprotection is unknown. We investigated whether sildenafil-induced acute cardioprotection is mediated by activation of mBKCa channels in the rat heart in vitro.MethodsMale Wistar rats (n = 8 per group) were randomized and anesthetized with pentobarbital (90 mg/kg). Hearts were isolated, mounted on a Langendorff system and perfused with Kr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 36 publications
2
30
0
1
Order By: Relevance
“…Due to the unexpected side effect of improvement of penile erection, in 1998, sildenafil citrate (Viagra ® ; Pfizer, Inc., New York, NY, USA) became the first PDE-5 inhibitor for the treatment of erectile dysfunction 8. Recently, sildenafil has shown benefits in experimental cardiac dysfunctions,9,10 tissue injury,1113 cystic fibrosis,14 and ischemia/reperfusion injury 15,16. Additionally, sildenafil as well as other PDE-5 inhibitors were shown to induce apoptosis in different human tumors, such as colon carcinoma and chronic lymphocyte leukemia 17,18.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the unexpected side effect of improvement of penile erection, in 1998, sildenafil citrate (Viagra ® ; Pfizer, Inc., New York, NY, USA) became the first PDE-5 inhibitor for the treatment of erectile dysfunction 8. Recently, sildenafil has shown benefits in experimental cardiac dysfunctions,9,10 tissue injury,1113 cystic fibrosis,14 and ischemia/reperfusion injury 15,16. Additionally, sildenafil as well as other PDE-5 inhibitors were shown to induce apoptosis in different human tumors, such as colon carcinoma and chronic lymphocyte leukemia 17,18.…”
Section: Introductionmentioning
confidence: 99%
“…Surgical preparation was performed as described previously [13,34]. Briefly, male Wistar rats were anesthetized by intraperitoneal injection of 90 mg/kg pentobarbital and decapitated.…”
Section: Surgical Preparationmentioning
confidence: 99%
“…Previously, we demonstrated that the lowest cardioprotective concentration of Ramelteon is 0.03 µM [8]. The concentration of the respective inhibitors of PKG (KT5823) and Akt (MK2206) was taken from the literature [13,23]. The inhibitors and Ramelteon were administered before global ischemia and reperfusion ( Figure 3A).…”
Section: Experimental Protocolmentioning
confidence: 99%
See 2 more Smart Citations